THE RELATIONSHIP BETWEEN DENTAL TECHNICIAN COMMUNICATION AND DENTIST SATISFACTION WITH THE COLOR OF FIXED DENTURE - Farah Aida Putri; Rahmad Arifin; Rosihan Adhani; Ika Kusuma Wardani; Bayu Indra Sukmana (FKG ULM, 2025)
Background: The high rate of tooth loss increases the demand for the fabrication of dentures, both fixed dental prostheses (FDP) and removable dental prostheses (RDP). Anterior tooth loss causes aesthetic and phonetic disturbances, so rehabilitation using a denture is needed. In aesthetics, color is one of the things that need to be considered, if the color of the resulting denture is not suitable, it will result in dissatisfaction. Color accuracy depends on effective communication between dentists and dental technicians. Research by Natassa J & Ayuningsih R stated that there were 51.7% of dentists who were dissatisfied with laboratory made results. Lack of communication can lead to dissatisfaction with the results of a fixed dental prostheses. Purpose: Knowing the relationship between dental technician communication and dentist satisfaction with denture color. Methods: This study used an analytic observational design with a cross sectional approach. The samples in this study were 40 dentists in the Banjarmasin area and 7 laboratories where dentures were made by Banjarmasin dentists selected using simple random sampling. Data collection was carried out by distributing questionnaires. Data analysis using the Spearman correlation test. Results: The results of data analysis using the Spearman correlation test produced data with a significance value of 0.00 (?<0.05). The correlation coefficient value in the study was found to be 0.523, indicating a significant relationship between the two variables. Conclusion: There is a significant relationship with a moderately strong relationship between the communication of dentists and dental technicians with dentists satisfaction with the color of dentures in Banjarmasin. Keywords: communication, dentist satisfaction, dental technician, dentist, fixed denture color